The influence of musical renres on putting accuracy in golf: An exploratory study - Baghurst, T.; Tapps, T.; Boolani, A.; Jacobson, B. H.; Gill, R. (Journal of Athletic Enhancement, 2014)
It is well documented that music can positively impact athletic performance with faster tempo music generally leading to improved outcomes. However, the benefit of music in fine motor control situations is relatively unknown. Therefore, this study sought to determine whether golf putting accuracy could be improved by listening to music and various musical genres. Participants were 22 (8 male, 14 female) university Division 1 golfers of average age 20.3 years and all with a minimum of 8 years of golf experience. Each participant completed a series of 6 trials which comprised of attempting 5 putts at 4 pre-designated locations around a hole. In a randomized order, participants were required to listen to no music or classical, country, rock, jazz, and hip hop/rap music while putting. A one-way ANOVA revealed a significant difference between no music compared to jazz (F(6,15) = 14.47, p = 0.001), hip hop/rap (F(6,15) = 4.55, p = 0.008), classical (F(6,15) = 4.33, p = 0.01), and country (F(6,15) = 2.82, p = 0.048). Rock music was not significant but approached significance (F(6,15) = 2.67, p = 0.058). A second one-way ANOVA compared musical genres to each other, and participants were found to perform significantly better while listening to jazz as opposed to any other musical genre (F(1,20) = 5.04, p = 0.036). There was no statistical significance between the male putters and female putters (F(5,2) = 6.55, p = .138). Music appears to improve golf putting performance over no music, but music genre can also significantly impact outcomes where jazz appears to be the most effective genre for this group. Future research is needed with a larger sample and other fine motor skill sports such as shooting or archery should investigate whether music and specific genres can influence performance.